PENERAPAN DAN PENGAMALAN HADIS DALAM PENGAJIAN LDII DI JALAN MANGAAN IV LORONG RAHAYU GANG MELATI KELURAHAN MABAR HILIR KECAMATAN MEDAN DELI SUMATERA UTARA (STUDI ANALISIS LDII) - Utami, Efdillah Putri (UIN Sumatera Utara Medan, 2020)
This study examines the application and practice of hadith in the study of LDII on Jalan Mangaan IV Lorong Rahayu. Melati Alley, Mabar Hilir, Medan Deli, North Sumatra, and briefly explained the history of LDII recitation. The purpose of this study is to find out how the application and practice of hadith in LDII study on Jalan Mangaan IV Lorong Rahayu. Melati Gang, Mabar Hilir, Medan Deli, North Sumatra. This study also aims to explain understanding a hadith correctly. The method used in this thesis research is descriptive approach method, qualitative method, and subject determination. The method used for data collection is the questionnaire, observation, interview, and library research methods. The results of the research conducted raised a number of themes discussed in this thesis, namely: the history of LDII development, the method of studying hadith, the traditions applied and practiced LDII worshipers, LDII congregation understanding of a hadith, goals, vision, mission, and LDII's motto, Opinion of figures and the public about LDII in Jalan Mangaan IV Lorong Rahayu. Melati Gang, Mabar Hilir, Medan Deli, North Sumatra